AMORIS LAETITIA IN DIFFERENT CULTURES - Vellguth, Klaus (Asian Horizons, 2017)
The debate on marriage and the family goes hand in hand with ecclesiological endeavours to fashion a thriving universal Church in the post-colonial era of globalisation. One of the issues involved is the development of a mutually respectful, intrapersonally authentic moral theology which is interpersonal and intercultural but not binding. There is a need to develop and jointly learn about processes so that, at the family synods and in the Post-Synodal Exhortation Amoris Laetitia, there can be discussion marked by intercultural respect of questions concerning the cultural shaping of the family and the inculturation of traditional concepts of marriage and the family. In the universal Church debate about marriage and the family there is finally also the question of the inculturation of the faith of the Church and of the appropriate handling of culturally influenced moral theological approaches in different contexts. The universal Church debate on marriage and the family and the two family synods are a source of encouragement to engage in a departure of an experimental nature and to make further endeavours with a view to enabling the universal Church to constantly reassess its position in a universal Church polylogue.